HOW DO FINANCIAL RATIOS AND OTHER VARIABLES CONTRIBUTE TO FINANCIAL STATEMENT FRAUD RISKS? - Dominikus, William; Effendi, Muhammad Arief; Palliam, Ralph (Fakultas Ekonomi dan Bisnis Universitas Trisakti, 2025)
This study investigates the influence of financial ratios and various additional factors on the fraudulent financial statements of non-financial companies listed on the Indonesia Stock Exchange from 2018 to 2021. The research examines several independent variables pertinent to fraudulent financial statements, including activity ratios, asset composition, leverage, liquidity, profitability, frequency of audit committee meetings, financial stability, and the nature of the industry. The study comprises a sample of 556 data points drawn from 139 companies selected based on specific criteria. Logistic regression was employed as the methodology for hypothesis testing. The findings indicate that financial stability significantly positively impacts the likelihood of fraudulent financial statements, as management may endeavour to stabilise financial conditions to obscure actual circumstances through fraudulent practices. Conversely, the frequency of audit committee meetings demonstrates a significant negative effect on the probability of fraudulent financial statements, as effective oversight can enhance the integrity of the reporting process. In contrast, the variables of activity ratios, asset composition, leverage, liquidity, profitability, and the nature of the industry do not significantly affect the likelihood of fraudulent financial statements. The implications of this research underscore the importance of robust corporate governance practices for practitioners, highlighting the necessity for vigilant oversight mechanisms to mitigate the risk of financial misreporting. These findings imply that firms should prioritize strengthening audit committee functions and ensuring financial transparency to reduce fraud risks. Regulators and stakeholders must emphasize frequent, effective oversight and promote governance standards. Companies must also foster ethical financial practices, as robust governance mechanisms play a crucial role in safeguarding the credibility of financial reporting and investor trust.